The Effect of Tax Avoidance and Tax Evasion on the Performance of South African Economy - Mvunabandi, Jean Damascene; Nomala, Bomi; Marimuthu, Ferina (International Journal of Economics and Financial Issues, 2024)
Using a quantitative longitudinal trends analysis, this study analysed the link between tax evasion and avoidance. The main aim was to assess the implications of evasion and avoidance of taxes on South African economy progress from 1994-2021. Publically secondary data available from South African Revenue authority were gathered. The data gathered provided us with basis of longitudinal statistical analysis of the extent of tax evasion and or tax avoidance affected the economic growth in the years 1994-2021. The Eviews 10 Results was used to estimate elasticities and buoyancies for major taxes with respect of South Africa’s economic growth for years 1994-2021. The natural logarithm of the gap between total budgeted tax income and realised tax income was also employed as a metric of tax evasion and avoidance in South Africa for this key research work. Ordinary Least Squares Regression (OLS) regression analysis was employed to evaluate whether the link between Gross Domestic Product (GDP) and tax evaded and avoided is strong or weak. Test for stationarity to see whether the parameter does not vary over time and for OLS was performed. The overall analysis of tax evasion and avoidance upon South African economy showed the increased tax revenue resulted in surpluses between tax revenue budgeted, tax revenue collected and economic growth (GDP), meaning tax evasion and avoidance in South Africa are minimal. The study's findings disprove prior studies that suggest that tax evasion and tax avoidance seriously affect Gross Domestic Products (GDP) and refute the null hypothesis of this study. However, the study’s results further revealed that increasing tax rates was said to have triggered a positive trend towards economic growth or GDP (actual revenue collected is more than expected taxation revenue annually to cover tax evaded and avoided. As far as policy is concerned the conclusion is reassuring that tax evasion and avoidance has minimal effect upon economic growth as long as tax rates are being risen. The results of this study provide implications for government that specific insights should allow policy makers to gain a better understanding on the key variables that are potentially associated with tax evasion and avoidance. Finally, the study contributes knowledge that is pertinent to an emerging country and provides much needed insights into the magnitude of the extent of tax evasion and avoidance on the county’s economic growth progress.